The ecosystem of a fallen tree - Pascoe, Elaine; Kuhn, Dwight (New York : PowerKids Press, 2003)
Describes the plant and animal life associated with a fallen tree, all of which create a miniature, co-dependent ecosystem.
Includes index.
Keywords: Animal ecology -- Juvenile literature; Trees -- Ecology -- Juvenile literature; Dead trees -- Juvenile literature; Trees; Habitat (Ecology); Ecology